New and old technologies in the Act of 26 January 2023 amending the Electoral Code Act and certain other acts (Journal of Laws of 2023, item 497) (Discourse of Law and Administration, 2024)
The changes introduced by the Act of January 26, 2023 amending the Electoral Code and some other acts ( Journal of Laws of 2023, item 497) can be somewhat perversely described as new and old technologies in the electoral process; The Central Register of Voters, introduced in place of the voter registers kept by the communes, is undoubtedly a solution that fits in with the trend of using new technologies to optimize the activities of public administration. Both public administration and voters are to be the beneficiaries of the Central Register of Voters. However, a specific cost is the question about the security of the register, the exercise of actual supervision over it and the dispersion of responsibility for the proper conduct of a process that is crucial for the functioning of the state: democratic elections. On the other hand, the amendment significantly increased the number of permanent voting circuits, which results in the need to establish a larger number of precinct electoral commissions, whose functioning in the system of electoral authorities is both necessary and problematic. Verification of the adopted solutions: „new” and „old” will take place in the conditions of a nationwide election campaign in 2023.
Keywords: electoral code; precinct electoral commission; central register of voters; new technologies